The Effect of Acetylation on Mechanical Properties of Biodegradable Plastic Made from Hipere Starch - Chesiana; Aritonang, Winda; Supeno; Asmuruf, Frans A. (SOTVI, 2024)
The study addresses the global problem of pollution caused by the long-term decomposition of plastic waste. It aims to explore the development of biodegradable plastics using Hipere starch and glycerol as a sustainable alternative, emphasizing their potential environmental benefits, abundance, and low cost. The primary materials used are Hipere starch, a natural polymer derived from plants, and glycerol as a plasticizer. These were selected for their compatibility and effectiveness in creating biodegradable plastics. Biodegradable plastics were synthesized through an acetylation process that modifies the starch, aiming to enhance its properties. Various concentrations of starch were tested to evaluate their impact on mechanical and physical characteristics. A soil burial test was conducted to assess biodegradability by monitoring mass reduction over seven days. The resulting plastics exhibited transparency, lightweight properties, insolubility in water, and mold-conforming shapes. Mechanical properties, including tensile strength and elongation, improved with higher starch concentrations. The soil burial test showed consistent mass reductions between 1-3% daily, with the most significant reduction occurring on day 7, demonstrating biodegradability. While improvements were observed, further research is needed to enhance mechanical properties by incorporating additional polymers or alternative modification techniques. This could expand the applications and durability of biodegradable plastics in various industries.